Avaliação da influência da geometria e dinâmica do escoamento de floculadores helicoidais na redução de turbidez utilizando modelagem física - Silva, Raphaela Cunha da (2007)
The flocculation is the stage of water treatment where destabilizeds colloidal particles, for coagulants agents, agglutinating forming floccs. These floccs are removed, later, for sedimentation or flotation. Amongst the hydraulical flocculators, the tubular helical flocculator is distinguished, pioneering studied for Grohmann, Reiter and Wiesmann in 1981, and still little explored. Being thus, in this work it was objectified to evaluate the effect of geometric and hydrodynamic parameters on the performance of process of tubular helical flocculator, being used physical modeling as tool. Moreover, to perfect the model of estimate of flocculation efficiency for tubular helical flocculators developed by Pelissari (2006). In the experiments, a synthetic water, stored in a tank, fed the hydraulical circuit, in accordance with outflow to be studied. This water left the tank and flowed off in direction to the reactor (tubular helical flocculator), in it was added to the chemical products, for run down of solid particles. Later, this mixture passed for the tubular helical flocculator, where there are the floccs formation (agglutination of destabilizeds particles) and them, it arrived at the decanter, where these floccs are deposited. In the decanter exit the water samples were collected for the evaluation of the efficiency of turbidity removal. The analysis of the results showed that the best efficiencies had been gotten for the lesser levels of energy, that is, minors hf, G, Ca, Re, Dn and Gn, therefore when these increases, the intensity of mixture of the system also increases, occurring, then, the flocc rupture or its not formation, due to bigger intensity of shock between particles. In relation to the perfectioning of the equation proposal for Pelissari (2006) for calculate the flocculation efficiency, had been made other analyses (dimensional and of multiple regression), considering news variables and experimental procedures. As result, an increase in the correlation between the data, measured and esteem was gotten, of 0,4500 for 0,9526 and a reduction of the average relative error of 17% for 2%, indicating that the variables used are well adjusted to the model considered for estimate of the flocculation efficiency.